Peripheral Retinal Neovascularization in a Patient with Sarcoidosis and Cocaine-Associated Autoimmunity - Ramak Roohipourmoallai; Samaneh Davoudi; Seyed Majid Hosseinian Benvidi; Siva S. R. Iyer (Case Reports in Ophthalmological Medicine)
A 63-year-old African-American female with history of sarcoidosis (lymph node biopsy proven) and cocaine abuse for 8 years was referred to us because of new floater. Her ocular history was unremarkable except for vague complaints of visual disturbance during a hospital admission in 2016. On presentation, her visual acuity was 20/400 in the right eye and 20/30 in the left eye. Dilated fundus exam and multimodal imaging showed thick epiretinal membrane (ERM) superior to optic nerve head causing a lamellar macular hole and intra retinal edema in the right eye, a full thickness macular hole, and peripheral neovascularization in the left eye. Peripheral vasculitis was appreciated in both eyes and peripheral neovascularization in the left eye on fluorescein angiography. The patient underwent laser therapy, and the new vessels regressed in the left eye without any changes in systemic medications. Multiple factors may contribute to retinal vasculitis and neovascularization including sarcoidosis, cocaine abuse, and other undiagnosed systemic vasculitis, which makes this case a mystery.